Teca Manaus: os processos de importação do terminal de cargas aeroportuário - Nascimento, Rafael Ferreira do (Brasil, 2023)
This study was based on the import processes of the Manaus Airport Cargo Terminal - TECA, which has been essential not only for the support of the air modal, but for the entire national and international economic scenario with active participation in the development of world heritage supplying the industrial hub of Manaus. TECA deals with import, export, national cargo and internment of cargo. Moving considerable revenues with high value-added services and cargo. It safely receives and handles the most varied types of cargo and products, has handling equipment suitable for any demand and has a computerized storage management system that meets its internal activities with its extremely complex and well-structured logistics. This research aims to detail the processes of receipt, handling, storage and release of cargo in the Import Sector of TECA Manaus, describing the activities of the logistics flow and mentioning the processes governed by customs laws. The study was based on exploratory and descriptive research. In this way, the case study was used to bring the results closer to reality. As for the results, the study can help in the understanding and importance of the TECA Manaus airport logistics chain, allowing to propose alternatives to improve its performance, in view of the scarcity of data on the sector, helping in the identification and analysis of any bottleneck or improvement in the processes and procedures for the elaboration of future academic studies.